Endocervical Regulatory T Cells Are Associated With Decreased Genital Inflammation and Lower HIV Target Cell Abundance - Ssemaganda, Aloysious; Cholette, Francois; Perner, Michelle; Kambaran, Cheli; Adhiambo, Wendy; Wambugu, Peter M.; Gebrebrhan, Henok; Lee, Amy; Nuhu, Faisal; Mwatelah, Ruth S.; Jahan, Naima; Omole, Tosin E.; et al. (Frontiers in Immunology, 2021)
Background. Regulatory T cells (Tregs) play important roles in tissue homeostasis, but few studies have investigated tissue Tregs in the context of genital inflammation, HIV target cell density, and vaginal microbiota in humans. Methods. We carried out a cross-sectional study in female sex workers from Nairobi (n=64). Systemic and cervicovaginal T cell subsets were enumerated using flow cytometry, cytokines measured in cervicovaginal secretions using multiplex ELISA, and vaginal microbiota profiled using 16S rRNA sequencing. Multivariable models tested for immune associations of cervicovaginal Treg frequency, adjusting for covariates. Results. The proportion of CD4+ CD25+ CD127low Tregs in the endocervix correlated with those in blood (r=0.31, p=0.01), with a higher Treg frequency observed in the endocervix (median 3.8 vs 2.0%, p<0.0001). Most Tregs expressed FoxP3 in both compartments, and CTLA-4 expression was higher on endocervical Tregs compared to blood (median 50.8 vs 6.0%, p<0.0001). More than half (34/62, 55%) of participants displayed a non-Lactobacillus dominant vaginal microbiota, which was not associated with endocervical Tregs or CD4+ T cell abundance. In a multivariable linear regression, endocervical Treg proportions were inversely associated with the number of elevated pro-inflammatory cytokines (p=0.03). Inverse Treg associations were also observed for specific cytokines including IL-1β, G-CSF, Eotaxin, IL-1RA, IL-8, and MIP-1β. Higher endocervical Treg proportions were associated with lower abundance of endocervical CD4+ T cells (0.30 log10 CD4+ T cells per log10 Treg, p=0.00028), with a similar trend for Th17 cells (p=0.09). Conclusions. Selectively increasing endocervical Tregs may represent a therapeutic pathway to reduce genital tract inflammation in women.